Terabit-Rate Transmission Using Optical Frequency Comb Sources - Pfeifle, Jörg (Karlsruhe Series in Photonics and Communications / Karlsruhe Institute of Technology, Institute of Photonics and Quantum Electronics (IPQ), 2017)
Energy-efficient Tbit/s optical interconnects are key elements for future communication systems. Three novel optical frequency comb sources are investigated, which have the potential of being integrated in chip-scale Tbit/s transmitters. Such frequency combs provide a large number of carriers. The equidistance of the comb lines helps to minimize spectral guard bands. For each type of comb source, coherent data transmission experiments show the potential for Tbit/s data transmission rates.